Ultra-high performance concrete for light bridge deck slab and preparation method of ultra-high performance concrete

By using composite cement and composite admixtures, combined with self-healing aggregates and POM fibers, and using self-made polycarboxylate water-reducing agents and composite expansion agents, the problems of high density and low strength of existing high-performance concrete have been solved, and low-density concrete has been prepared. Ultra-high performance concrete for lightweight bridge decks with bulk density, high strength and low shrinkage has self-healing function and is suitable for bridge engineering.

CN119330676AActive Publication Date: 2025-01-21GANSU ROAD & BRIDGE CONSTR GROUP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411493990.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing high-performance concrete has high density, low strength, and is prone to cracking, resulting in construction difficulties and increased repair workload, limiting the development and application of bridges.

Method used

Portland cement and ferroaluminate cement are used as composite cement, activated metakaolin powder, ultrafine fly ash, and microsilica fume are added as composite admixtures, and self-repairing aggregates and POM fibers are used, and homemade polycarboxylic acid is used Acid water reducing agent and composite expansion agent control the construction performance of concrete.

Benefits of technology

Ultra-high performance concrete for lightweight bridge decks with low bulk density, high strength, and low shrinkage has been prepared. It has a self-healing function, reduces the dead weight of the bridge deck, and improves the structural stability and construction convenience of the bridge.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to ultra-high performance concrete for a light bridge deck and a preparation method thereof.Portland cement and aluminoferrite cement are adopted as composite cement, active metakaolin powder, superfine fly ash and silica fume are added as composite admixtures, and self-repairing aggregate and POM fiber are matched to prepare the ultra-high performance concrete for the light bridge deck. The self-made polycarboxylic acid water reducer is added to control the construction performance of the concrete, and the composite expanding agent is added, so that the ultra-high performance concrete with low volume weight, high strength and low shrinkage for the light bridge deck is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to ultra-high performance concrete for lightweight bridge decks and a preparation method thereof. Background Art

[0002] The continuous development of the transportation and logistics industries has driven the rapid development of bridge engineering and marine engineering in the engineering community, and large-span bridges have continued to break engineering records.

[0003] However, ordinary high-performance concrete currently has high density, low strength, and a high water-cement ratio, which makes it easy to crack, causing construction difficulties and increased repair workload, limiting the development and application of bridges.

[0004] Therefore, there is an urgent need to develop ultra-high performance concrete materials for lightweight bridge decks that are lightweight, high-strength, self-repairing, volume-stable and easy to construct, so as to further reduce the deadweight of bridge structures, increase bridge spans, and enable rapid construction and later use to meet ever-increasing construction needs. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, the present invention provides an ultra-high performance concrete for lightweight bridge decks. Specifically, the present invention adopts silicate cement and ferroaluminate cement as composite cement, adds active kaolin powder, ultrafine fly ash, and microsilica powder as composite admixtures, and combines self-repairing aggregate and POM fiber, adds a homemade polycarboxylate water reducer to control the concrete construction performance, and adds a composite expansion agent to prepare ultra-high performance concrete for lightweight bridge decks with low bulk density, high strength, and low shrinkage.

[0006] Specifically, the ultra-high performance concrete for lightweight bridge deck of the present invention is composed of the following raw materials in parts by weight:

[0007] 600-650 parts of silicate cement, 50-100 parts of ferroaluminate cement, 100-120 parts of active kaolin powder, 120-180 parts of ultrafine fly ash, 100-150 parts of microsilica powder, 700-900 parts of self-healing aggregate, 15-20 parts of active calcium oxide, 5-10 parts of active magnesium oxide, 25-30 parts of POM fiber, 24-30 parts of polycarboxylate water reducer, and 320-350 parts of water.

[0008] The present invention adopts silicate cement and ferroaluminate cement as composite cement, adds active kaolin powder, ultrafine fly ash and microsilica powder as composite admixtures, has excellent hydration activity and provides guarantee for the mechanical properties of concrete; and adopts active calcium oxide and active magnesium oxide as composite expansion agents to offset the shrinkage of concrete.

[0009] Preferably, the self-repairing aggregate preparation process is:

[0010] a. Mix 80-90 parts of porous silicate powder and 5-10 parts of sodium carbonate, heat and calcine, keep warm, and quench to obtain a modified porous silicate powder.

[0011] b. Mix 50-75 parts of steel slag powder, 35-45 parts of modified porous silicate powder, 8-15 parts of silicate cement and 2-5 parts of microsilica powder to obtain powder.

[0012] c. Add 95-105 parts of powder to the drum granulator, slowly spray 18-25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0013] d. Carbonize and cure the blank, dry it, soak it in water glass in a vacuum, and dry it naturally.

[0014] The self-repairing aggregate prepared by the present invention has relatively more interconnected pores, and the crushing resistance of the self-repairing aggregate is enhanced after carbonization curing, and it has the effect of light weight and high strength. POM fiber is used to replace steel fiber, which greatly reduces the bulk density of ultra-high performance concrete, and can reduce the load on the bridge caused by the deadweight of the bridge deck. In addition, the self-repairing aggregate encapsulates water glass, and the water glass is encapsulated inside the aggregate as the main self-repairing agent and stimulator. During the drying process, it reacts with CO2 in the air to form surface inert closed capsules. During the mixing process of ultra-high performance concrete, the surface passivation film is broken, and the internal water glass is released to promote the hydration of the admixture. In particular, the water glass has a strength stimulating effect on the reaction of active kaolin, thereby improving the strength of ultra-high performance concrete.

[0015] At the same time, the present invention adopts a lower water-cement ratio, which can also promote the improvement of concrete strength. The lower water-cement ratio will also retain part of the cementitious material without hydration. When microcracks appear in the ultra-high performance concrete, the invasion of moisture and water vapor allows the self-repairing aggregate to release sodium silicate solution, which re-stimulates the hydration activity of the cementitious material, causing hydration reaction and healing the microcracks.

[0016] Preferably, the polycarboxylic acid water reducer is polymerized with 15-20 parts of acrylic acid, 70-80 parts of methyl allyl alcohol polyoxyethylene ether, 3-8 parts of sodium methyl propylene sulfonate, and 2-4 parts of methacrylate-2-hydroxyethyl phosphate as monomers.

[0017] In order to improve the construction performance of concrete prepared with high cementitious materials, low water-cement ratio and self-repairing aggregate, the present invention prepares a special polycarboxylic acid water reducer to ensure the workability of ultra-high performance concrete slurry.

[0018] Preferably, the silicate cement is P·II52.5 cement.

[0019] Preferably, the active metakaolin powder is made by grinding kaolin after calcination at 850°C, and has a specific surface area of ​​≥800m2 / kg.

[0020] Preferably, the specific surface area of ​​the ultrafine fly ash is ≥1500m 2 / kg, 28d activity index ≥100%.

[0021] Preferably, the microsilica powder is single crystal microsilica powder with a specific surface area of ​​≥18000m 2 / kg, SiO2 content ≥96%.

[0022] Preferably, in the self-repairing aggregate preparation process, the porous silicate powder in step a is diatomaceous earth, containing SiO2 with a mass fraction of 88.95%, an average pore diameter of 56.2 nm, a particle size ≤0.075 mm, and a loss on ignition of 0.39%.

[0023] Preferably, in the process for preparing the self-repairing aggregate, the temperature is raised to 900-1100° C. for calcination in step a, and the holding time is 1-2 h.

[0024] Preferably, in the self-repairing aggregate preparation process, in the carbonization curing in step d, the carbonization pressure is 0.1-0.5 MPa, the temperature is 20-24° C., the relative humidity is 50-70%, and the carbonization curing time is 24-48 h.

[0025] Preferably, in the process for preparing the self-repairing aggregate, in step d, the modulus of water glass is 1.3-1.5, the mass concentration is 30-35%, and the vacuum immersion time is 10-20 min.

[0026] The present invention also relates to a method for preparing the ultra-high performance concrete for the lightweight bridge deck, which specifically comprises the following steps:

[0027] 1) Weigh each raw material by weight,

[0028] 2) Add the self-repairing aggregate and some water into the mixer to mix and pre-wet.

[0029] 3) Add silicate cement, ferroaluminate cement, active kaolin powder, ultrafine fly ash, microsilica powder, active calcium oxide, and active magnesium oxide into a box mixer and mix evenly. Add POM fiber and mix evenly.

[0030] 4) Mix the polycarboxylate water reducer and the remaining water evenly to obtain an admixture solution.

[0031] 5) Add the additive solution into the mixer and mix well to obtain slurry.

[0032] 6) Shape and cure the slurry to obtain the product.

[0033] Preferably, the curing adopts standard curing.

[0034] The present invention has the following technical advantages:

[0035] 1. The present invention adopts composite admixtures and composite cement, and reduces the water-binder ratio to ensure the mechanical properties of concrete.

[0036] 2. The present invention uses self-repairing aggregate to exert its self-repairing function. After micro-cracks occur in the concrete, the strength can be partially restored by curing in a humid environment.

[0037] 3. The use of the self-repairing aggregate and organic fiber of the present invention can effectively reduce the density of concrete, and has the characteristics of high strength and low shrinkage, which is conducive to promoting efficient application in fields such as bridges, marine engineering and other structural engineering that have higher requirements on the deadweight of the structure. DETAILED DESCRIPTION

[0038] In order to characterize the technical effect of the present invention, concrete was prepared and its performance was tested. During the test, the silicate cement used was P·Ⅱ52.5 cement, and the active metakaolin powder was made by grinding kaolin calcined at 850℃ with a specific surface area of ​​850m 2 / kg, the specific surface area of ​​ultrafine fly ash is 1600m 2 / kg, 28d activity index is 105%, the microsilica powder is single crystal microsilica powder, the SiO2 content is 96%, the porous silicate powder is diatomaceous earth from Linjiang City, Jilin Province, containing SiO2 mass fraction of 88.95%, average pore diameter of 56.2nm, particle size ≤0.075mm, loss on ignition 0.39%, water glass modulus of 1.5, and mass concentration of 30%.

[0039] Example 1

[0040] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0041] 620 parts of silicate cement, 60 parts of ferroaluminate cement, 100 parts of active kaolin powder, 160 parts of ultrafine fly ash, 110 parts of microsilica powder, 850 parts of self-repairing aggregate, 18 parts of active calcium oxide, 7 parts of active magnesium oxide, 26 parts of POM fiber, 27 parts of polycarboxylate water reducer, 340 parts of water,

[0042] The self-repairing aggregate preparation process is:

[0043] a. Mix 80 parts of porous silicate powder and 6 parts of sodium carbonate, heat to 1000℃ and calcine, keep warm for 1.5h, and cool rapidly to obtain modified porous silicate powder.

[0044] b. Mix 75 parts of steel slag powder, 45 parts of modified porous silicate powder, 12 parts of silicate cement and 2 parts of microsilica powder to obtain powder.

[0045] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0046] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, dry it, soak it in water glass vacuum for 15 minutes, and dry it naturally.

[0047] The polycarboxylic acid water reducer is prepared by polymerizing 20 parts of acrylic acid, 78 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of sodium methyl propylene sulfonate and 4 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

[0048] After testing, the initial expansion of concrete is 580mm, the expansion after 2h is 545mm, and the apparent density is 2016kg / m 3 , 28d compressive strength 145.3MPa, flexural strength 14.9MPa, tensile strength 7.4MPa, elastic modulus 38.4GPa, drying shrinkage 66×10 -6 .

[0049] Example 2

[0050] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0051] 640 parts of silicate cement, 70 parts of ferroaluminate cement, 100 parts of active kaolin powder, 130 parts of ultrafine fly ash, 150 parts of microsilica powder, 880 parts of self-repairing aggregate, 20 parts of active calcium oxide, 8 parts of active magnesium oxide, 28 parts of POM fiber, 29 parts of polycarboxylate water reducer, 340 parts of water,

[0052] The self-repairing aggregate preparation process is:

[0053] a. Mix 90 parts of porous silicate powder and 9 parts of sodium carbonate, heat to 1000°C for calcination, keep warm for 1.5h, and quench to obtain modified porous silicate powder.

[0054] b. Mix 60 parts of steel slag powder, 45 parts of modified porous silicate powder, 14 parts of silicate cement and 4 parts of microsilica powder to obtain powder.

[0055] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0056] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, dry it, soak it in water glass vacuum for 15 minutes, and dry it naturally.

[0057] The polycarboxylic acid water reducer is prepared by polymerizing 20 parts of acrylic acid, 75 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of sodium methyl propylene sulfonate and 3 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

[0058] After testing, the initial expansion of concrete is 570mm, the 2h expansion is 550mm, and the apparent density is 2034kg / m 3 , 28d compressive strength 147.0MPa, flexural strength 15.3MPa, tensile strength 8.1MPa, elastic modulus 39.2GPa, drying shrinkage 62×10 -6 .

[0059] Comparative Example 1

[0060] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0061] 640 parts of Portland cement, 70 parts of ferroaluminate cement, 100 parts of mineral powder, 130 parts of ultrafine fly ash, 150 parts of microsilica fume, 880 parts of self-repairing aggregate, 20 parts of active calcium oxide, 8 parts of active magnesium oxide, 78 parts of steel fiber, 29 parts of polycarboxylate water reducer, 340 parts of water,

[0062] The self-repairing aggregate preparation process is:

[0063] a. Mix 90 parts of porous silicate powder and 9 parts of sodium carbonate, heat to 1000°C for calcination, keep warm for 1.5h, and quench to obtain modified porous silicate powder.

[0064] b. Mix 60 parts of steel slag powder, 45 parts of modified porous silicate powder, 14 parts of silicate cement and 4 parts of microsilica powder to obtain powder.

[0065] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0066] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, dry it, soak it in water glass vacuum for 15 minutes, and dry it naturally.

[0067] The polycarboxylic acid water reducer is prepared by polymerizing 20 parts of acrylic acid, 75 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of sodium methyl propylene sulfonate and 3 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

[0068] After testing, the initial expansion of concrete is 550mm, the expansion after 2h is 500mm, and the apparent density is 2510kg / m 3, 28d compressive strength 128.4MPa, flexural strength 10.9MPa, tensile strength 6.3MPa, elastic modulus 37.0GPa, drying shrinkage 121×10 -6 .

[0069] Comparative Example 2

[0070] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0071] 640 parts of silicate cement, 70 parts of ferroaluminate cement, 100 parts of active kaolin powder, 130 parts of ultrafine fly ash, 150 parts of microsilica powder, 880 parts of 2.36-4.75mm pottery sand, 20 parts of active calcium oxide, 8 parts of active magnesium oxide, 28 parts of POM fiber, 29 parts of polycarboxylate water reducer, 340 parts of water,

[0072] The polycarboxylic acid water reducer is prepared by polymerizing 20 parts of acrylic acid, 75 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of sodium methyl propylene sulfonate and 3 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

[0073] After testing, the initial expansion of the concrete was 540mm, there was no fluidity after 2 hours, and the apparent density was 2130kg / m 3 , 28d compressive strength 92.6MPa, flexural strength 8.7MPa, tensile strength 5.9MPa, elastic modulus 34.3GPa, drying shrinkage 115×10 -6 .

[0074] Comparative Example 3

[0075] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0076] 640 parts of silicate cement, 70 parts of ferroaluminate cement, 100 parts of active kaolin powder, 130 parts of ultrafine fly ash, 150 parts of microsilica powder, 880 parts of self-repairing aggregate, 20 parts of active calcium oxide, 8 parts of active magnesium oxide, 28 parts of POM fiber, 29 parts of polycarboxylate water reducer, 340 parts of water,

[0077] The self-repairing aggregate preparation process is:

[0078] a. Mix 90 parts of porous silicate powder and 9 parts of sodium carbonate, heat to 1000°C for calcination, keep warm for 1.5h, and quench to obtain modified porous silicate powder.

[0079] b. Mix 55 parts of modified porous silicate powder, 34 parts of silicate cement and 24 parts of microsilica powder to obtain powder.

[0080] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0081] d. The blank is cured for 24 hours, dried, and soaked in water glass vacuum for 15 minutes, and dried naturally.

[0082] The polycarboxylic acid water reducer is polymerized with 20 parts of acrylic acid, 75 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of sodium methyl propylene sulfonate and 3 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

[0083] After testing, the initial expansion of concrete is 550mm, the expansion after 2h is 500mm, and the apparent density is 2170kg / m 3 , 28d compressive strength 102.4MPa, flexural strength 11.7MPa, tensile strength 6.6MPa, elastic modulus 36.0GPa, drying shrinkage 98×10 -6 .

[0084] Comparative Example 4

[0085] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0086] 640 parts of Portland cement, 70 parts of sulphoaluminate cement, 100 parts of active kaolin powder, 130 parts of ultrafine fly ash, 150 parts of microsilica fume, 880 parts of self-repairing aggregate, 28 parts of UEA expansion agent, 28 parts of POM fiber, 29 parts of polycarboxylate water reducer, 340 parts of water,

[0087] The self-repairing aggregate preparation process is:

[0088] a. Mix 90 parts of porous silicate powder and 9 parts of sodium carbonate, heat to 1000°C for calcination, keep warm for 1.5h, and quench to obtain modified porous silicate powder.

[0089] b. Mix 60 parts of steel slag powder, 45 parts of modified porous silicate powder, 14 parts of silicate cement and 4 parts of microsilica powder to obtain powder.

[0090] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0091] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, dry it, soak it in water glass vacuum for 15 minutes, and dry it naturally.

[0092] The polycarboxylic acid water reducer is polymerized with 20 parts of acrylic acid, 75 parts of methyl allyl alcohol polyoxyethylene ether, 5 parts of sodium methyl propylene sulfonate and 3 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

[0093] After testing, the initial expansion of concrete is 560mm, the expansion after 2h is 510mm, and the apparent density is 2095kg / m 3 , 28d compressive strength 133.8MPa, flexural strength 12.3MPa, tensile strength 7.0MPa, elastic modulus 36.2GPa, drying shrinkage 276×10 -6 .

[0094] Comparative Example 5

[0095] Concrete, characterized in that it is composed of the following raw materials in parts by weight:

[0096] 640 parts of silicate cement, 70 parts of ferroaluminate cement, 100 parts of active kaolin powder, 130 parts of ultrafine fly ash, 150 parts of microsilica powder, 880 parts of self-repairing aggregate, 20 parts of active calcium oxide, 8 parts of active magnesium oxide, 28 parts of POM fiber, 29 parts of polycarboxylate water reducer, 340 parts of water,

[0097] The self-repairing aggregate preparation process is:

[0098] a. Mix 90 parts of porous silicate powder and 9 parts of sodium carbonate, heat to 1000°C for calcination, keep warm for 1.5h, and quench to obtain modified porous silicate powder.

[0099] b. Mix 60 parts of steel slag powder, 45 parts of modified porous silicate powder, 14 parts of silicate cement and 4 parts of microsilica powder to obtain powder.

[0100] c. Add 100 parts of powder into the drum granulator, slowly spray in 25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets.

[0101] d. Carbonize and cure the blank for 24 hours in an environment with a pressure of 0.3MPa, a temperature of 20°C, and a relative humidity of 60%, dry it, soak it in water glass vacuum for 15 minutes, and dry it naturally.

[0102] The polycarboxylate water reducer is prepared by polymerizing 20 parts of acrylic acid, 78 parts of methyl allyl alcohol polyoxyethylene ether and 5 parts of sodium methyl propylene sulfonate as monomers.

[0103] After testing, the initial expansion of concrete is 600mm, the self-repairing aggregate floats slightly, there is no fluidity after 2 hours, and the apparent density is 2100kg / m 3 , 28d compressive strength 120.8MPa, flexural strength 10.9MPa, tensile strength 6.7MPa, elastic modulus 36.1GPa, drying shrinkage 173×10 -6 .

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultra-high performance concrete for a lightweight bridge deck, characterized in that: It is composed of the following raw materials in parts by weight: 600-650 parts of silicate cement, 50-100 parts of ferroaluminate cement, 100-120 parts of active kaolin powder, 120-180 parts of ultrafine fly ash, 100-150 parts of microsilica powder, 700-900 parts of self-repairing aggregate, 15-20 parts of active calcium oxide, 5-10 parts of active magnesium oxide, 25-30 parts of POM fiber, 24-30 parts of polycarboxylate water reducer, 320-350 parts of water, The self-repairing aggregate preparation process is: a. Mix 80-90 parts of porous silicate powder and 5-10 parts of sodium carbonate, heat and calcine, keep warm, and quench to obtain a modified porous silicate powder. b. Mix 50-75 parts of steel slag powder, 35-45 parts of modified porous silicate powder, 8-15 parts of silicate cement and 2-5 parts of microsilica powder to obtain powder. c. Add 95-105 parts of powder to the drum granulator, slowly spray 18-25 parts of water, and rotate to granulate to obtain 2.36-4.75mm billets. d. Carbonize and cure the blank, dry it, soak it in water glass vacuum, and dry it naturally. The polycarboxylic acid water reducer is prepared by polymerizing 15-20 parts of acrylic acid, 70-80 parts of methyl allyl alcohol polyoxyethylene ether, 3-8 parts of sodium methyl propylene sulfonate and 2-4 parts of methyl acrylate-2-hydroxyethyl phosphate as monomers.

2. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: The silicate cement is P·II52.5 cement.

3. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: The active metakaolin powder is made by grinding kaolin after calcination at 850°C, with a specific surface area of ​​≥800m 2 / kg.

4. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: The specific surface area of ​​the ultrafine fly ash is ≥1500m 2 / kg, 28d activity index ≥100%.

5. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: The microsilica powder is single crystal microsilica powder with a specific surface area of ​​≥18000m 2 / kg, SiO2 content ≥96%.

6. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: In the self-repairing aggregate preparation process, the porous silicate powder in step a is diatomaceous earth, containing SiO2 by mass fraction of 88.95%, an average pore diameter of 56.2nm, a particle size of ≤0.075mm, and a loss on ignition of 0.39%.

7. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: In the self-repairing aggregate preparation process, the temperature is raised to 900-1100° C. for calcination in step a, and the heat preservation time is 1-2 hours.

8. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: In the self-repairing aggregate preparation process, in step d, the carbonization pressure in the carbonization curing is 0.1-0.5 MPa, the temperature is 20-24° C., the relative humidity is 50-70%, and the carbonization curing time is 24-48 hours.

9. The ultra-high performance concrete for lightweight bridge deck according to claim 1, characterized in that: In the self-repairing aggregate preparation process, in step d, the water glass modulus is 1.3-1.5, the mass concentration is 30-35%, and the vacuum immersion time is 10-20 minutes.

10. The method for preparing ultra-high performance concrete for lightweight bridge deck according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Add the self-repairing aggregate and some water into the mixer to mix and pre-wet. 3) Add silicate cement, ferroaluminate cement, active kaolin powder, ultrafine fly ash, microsilica powder, active calcium oxide, and active magnesium oxide into a box mixer and mix evenly. Add POM fiber and mix evenly. 4) Mix the polycarboxylate water reducer and the remaining water evenly to obtain an admixture solution. 5) Add the additive solution into the mixer and mix well to obtain slurry. 6) The slurry is molded and cured.

Citation Information

Patent Citations

  • Viscosity-reducing polycarboxylic high efficiency solid water reducer, preparation and application thereof

    CN109721690A

  • Self-repairing aggregate and preparation method and application thereof

    CN110845169A

  • Efficient polycarboxylate superplasticizer and application thereof

    CN117720695A

  • Large-volume long-life concrete and preparation method thereof

    CN117819896A

  • Preparation method and application of self-repairing aggregate

    CN118439808A